Prognostic Value of P63 Expression in Muscle-Invasive Bladder Cancer and Association with Molecular Subtypes—Preliminary Report - Francesca Sanguedolce; Ugo Giovanni Falagario; Magda Zanelli; Andrea Palicelli; Maurizio Zizzo; Stefano Ascani; Simona Tortorella; Gian Maria Busetto; Angelo Cormio; Giuseppe Carrieri; Luigi Cormio (Current Issues in Molecular Biology, 2024)
There is an ongoing need for biomarkers that could reliably predict the outcome of BC and that could guide the management of this disease. In this setting, we aimed to explore the prognostic value of the transcription factor P63 in patients with muscle-invasive bladder cancer (MIBC) having undergone radical cystectomy. The correlation between P63 expression and clinicopathological features (tumor stage, nodes involvement, patterns of muscularis propria invasion, papillary architecture, anaplasia, concomitant carcinoma in situ, lymphovascular invasion, perineural invasion, necrosis) and molecular subtyping (basal and luminal type tumors) was tested in 65 radical cystectomy specimens and matched with cancer-specific survival (CSS) and overall survival (OS). P63-negative tumors displayed significantly higher rates of pattern 2 of muscularis propria invasion (50% vs. 14%, p = 0.002) and variant histology (45% vs. 19%, p = 0.022) compared to P63-positive ones. According to the combined expression of CK5/6 and CK20 (Algorithm #1), P63-positive and P63-negative tumors were mostly basal-like and double-negative, respectively (p = 0.004). Using Algorithm #2, based on the combined expression of CK5/6 and GATA3, the vast majority of tumors were luminal overall and in each group (p = 0.003). There was no significant difference in CSS and OS between P63-positive and P63-negative tumors, but the former featured a trend towards longer OS. Though associated with pathological features harboring negative prognostic potential, P63 status as such failed to predict CSS and OS. That said, it may contribute to better molecular subtyping of MIBC.